TINJAUAN PENGGUNAAN GPS SAAT MENGEMUDI OLEH PENGEMUDI TRANSPORTASI ONLINE DI KABUPATEN SLEMAN - Emilia Metta Karunia Wijaya (Justitia et Pax, 2021)
This legal paper writing discusses the use of GPS review by online transportation drivers in Sleman Regency. The formulation problem is how to the use of GPS review by online transportation drivers in Sleman Regency. This study uses a normative legal research method supported by interviews with resource persons. Regulations using GPS on online transportation drivers while driving is fulfilling philosophically and juridically. Unfortunately, this arrangement is not sociologically recognized by the community, so it has not to be accepted and implemented. The prohibition of using GPS for online transportation drivers while driving is not optimally implementing. This is because investigators have difficulty in cracking down on online transportation drivers who see GPS while driving.